KERANGKA PENELITIAN: MENUJU PENYELESAIAN STUDI DAN PENELITIAN KEAMANAN SIBER: RESEARCH FRAMEWORK: TOWARDS COMPLETION OF CYBERSECURITY STUDY AND RESEARCH - Melwin Syafrizal; Wahid MiftahuL Ashari; Mauludil Asri M Cane (LPPM Universitas Abdurrab, 2025)
This article presents a research framework in cybersecurity developed through a narrative literature review and conceptual analysis. The research process involved four phases: (1) a literature search using keywords related to